2012
DOI: 10.1261/rna.030270.111
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stress granule assembly in Schizosaccharomyces pombe

Abstract: Stress granules (SGs) are cytoplasmic aggregates of RNA and proteins in eukaryotic cells that are rapidly induced in response to environmental stress, but are not seen in cells growing under favorable conditions. SGs have been primarily studied in mammalian cells. The existence of SGs in the fission yeast and the distantly related budding yeast was demonstrated only recently. In both species, they contain many orthologs of the proteins seen in mammalian SGs. In this study, we have characterized these proteins … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
36
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 34 publications
4
36
1
Order By: Relevance
“…For example, we found that Ubp3 colocalizes with the stress granule marker Pbp1 in heatstressed cells. A similar association has been observed in S. pombe cells exposed to a heat stress (50). Furthermore, USP10 was observed to localize to stress granules in mammalian cells exposed to heat or arsenite stress (28).…”
Section: Discussionsupporting
confidence: 80%
“…For example, we found that Ubp3 colocalizes with the stress granule marker Pbp1 in heatstressed cells. A similar association has been observed in S. pombe cells exposed to a heat stress (50). Furthermore, USP10 was observed to localize to stress granules in mammalian cells exposed to heat or arsenite stress (28).…”
Section: Discussionsupporting
confidence: 80%
“…Images were acquired using a Leica DM RA2 microscope equipped with a Leica DC 350F camera and were assembled using Adobe PhotoShop. Image quantitation was done as described previously (11).…”
Section: Methodsmentioning
confidence: 99%
“…The two-step immunoglobulin G (IgG)-Sepharose and calmodulin resin affinity purification was carried out as described previously (11). The purified proteins were eluted with 20 mM EGTA to be precipitated with trichloroacetic acid (TCA) at a final concentration of 20%, separated on SDS-PAGE gels, and visualized by Sypro Ruby.…”
Section: Methodsmentioning
confidence: 99%
“…PABP is a marker of stress granules, RNA-enriched granules that are formed in response to certain stress conditions (38), whereas Hsp104 is a large molecular chaperone involved in protein quality control and disaggregation of various cytosolic protein aggregates (39). To further examine the nature of the observed Sdj1-L169P aggregates, the localization of Sdj1-L169P was analyzed in strains expressing mCherry-labeled PABP (Pab1) or Hsp104.…”
Section: Volume 290 • Number 34 • August 21 2015mentioning
confidence: 99%